Developing Intercultural Communicative Competence (ICC) of English majors in courses dealing with the culture of English-speaking countries - Laskowska, Martyna (Neofilolog, 2024)
UNESCO (2013: 16) describes “intercultural competences” as: (1) the necessary linguistic knowledge and awareness when interacting with people from different cultures; (2) relevant knowledge about specific cultures; (3) broad comprehension about the issues that arise when members of different cultures interact; (4) adaptable attitudes that encourage creating and sustaining contact with diverse members of society. The development of intercultural competence has increasingly been recognized as a vital aim of foreign language (L2) education. The aim of the study was to investigate the relationship between courses related to the culture of English-speaking countries and the development of intercultural communicative competence of English philology students. Specifically, it explores participants’ opinions on whether the culture courses support students’ ability to acquire academic-level communicative competence, fluency in formal and informal language, and a holistic understanding of the spectrum of Anglophone communities. The participants of the study were English philology students and lecturers teaching culture courses. A mixed methodology was used with two types of research methods: a student survey and semi-structured interviews with lecturers. The results of the study allow for a formulation of didactic implications for the development of intercultural competence of English philology students.